Studi Sistem Drainase Resapan di Wilayah Karang Anyar Kota Tarakan - Asta, Asta; Handayani, Rosmalia (Borneo Engineering : Jurnal Teknik Sipil, 2017)
Tarakan City is one city that is often flooded during the rainy season it is in because of the narrow drainage system and due to the accumulation of garbage other than one of the factors that affect flooding is tidal. For the central Tarakan Region, specifically in the region of Karang Anyar Central Tarakan that is Seroja , Kenanga and mawar street flood that occurred due to the drainage system which is not good. And population growth is rapidly increasing and the growth of residential construction and industry as well as other supporting facilities are not balanced with the development of the drainage system. Increase the number of discharges that come out due to the increase of housing and other buildings are often already do not meet the capacity of its maximum capacity on existing drainage channels. The research is conducted by doing a survey in the field to obtain primary data and secondary data which will then be processed using the method ISO No. 03- 2459-2002 about general and technical requirments infiltration wells, this standard is a revision of ISO No. 03-3459-2991. The result of the field trial showed that the infiltration rate as measured by the single ring infiltrometeron seroja street at 6cm/hour, on kenanga street by 6 cm/hour, and mawar street by 9cm/hour. Each infiltration wells are planned at each house is capable of reducing flood discharge as much as 0.00254m3/sec at seroja street, kenanga street 0.00282 m3/sec and 0.0034m3/sec on mawar street. Under the assumption 70 % of homes in the study area using infiltration wells.